(3CTQa GdNWGH dCTQa GdCbWGHs - (3HgGA GdOjf eMeO egOj GdUjGOj GdQaGYj GdMSjfj, GdQhGS , J (B1287 (3g` s
(3ChdgG (B:s
(3aLeYJ eG CdgeJ Hg ai gPg GdcQGSI hSejJgG (B( (3CTQa GdNWGH , dCTQa GdCbWGH (B) s
(3BNQgG (B:s
(3jG hSjdJfG Edi Gddg GdUdGI hGdSdGe Ydjc jG Chd Ndb Gddg hNGJe QSd Gddg GdUdGI hGdSdGe Ydjce jG CfHjGA Gddg CLejYf hGdMeO ddg QH GdYGdjef s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
(3GdXGgQjI (B(9298) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs